(untitled) (Ameghiniana, 2019)
Molar morphology is one of the most used proxies for paleoecological inferences in mammals. Since the 19th century, several authors associated some dental morphological traits with the diet of the animal by means of qualitative and descriptive analyses. Later on, since the last century, different studies of tooth function have associated various quantitative traits of tooth shape (i.e., morphometric ratios or angles) with the degree of vertebrate flesh consumed by the animal. However, because different inferences of diet for the same species can be found in the literature, it becomes crucial to carry on studies comparing the power of different proxies. In this work, we compared the utility of classic morphometric indices (RGA, AI and angle ?) and three-dimensional landmarks configuration regarding diet inferences. Based on a previously published dataset from our working group, we calculated the classic morphometric indices and performed three classification methods. Our results demonstrate that when using the scores of the landmarks configuration, the diet of species is better reclassified than when using morphometric indices. Furthermore, considering the intraspecific variation when making paleoecological inferences appears fundamental. In the perspective of inferring ecological characteristics to extinct animals, the consideration of the morphological variation in extant organisms is a safeguard to prevent from any misinterpretation in the recontruction of past ecologies. doi: 10.5710/AMGH.24.07.2019.3255